The Experience of Cervical Screening for Women With Physical Disabilities - Hanlon, Erin Portia (Auckland University of Technology, 2015)
Using Interpretive Description as an approach, this qualitative study explores and identifies what women with physical disabilities experience when attempting to access cervical screening services. Recent literature has focused on identified barriers associated with accessing services. Consequently there is limited knowledge within the New Zealand context surrounding aspects of cervical screening. This study aimed to explore what women were experiencing, aspects of their screening habits and if they did encounter barriers. Purposeful sampling strategies were used to drive recruitment. Semi-structured interviews were carried out with eleven women who participated in this study. A central theme and three sub-themes surfaced when exploring the women’s experiences: the theme of barriers joins with the three sub-themes in that women in New Zealand do experience barriers when attempting to undergo cervical screening. The framework of barriers were organised into sub-themes such as structural, physical, systematic and attitudinal. Although, these participants encountered barriers, they were able to overcome the barriers and engage with screening services. In sharing their experiences, the participants identified aspects of clinician’s behaviour that allowed them to engage in services. Also, these participants indicated that they had created support systems in order to continue their health maintenance. This study found that these women were both confronted with barriers but were able to overcome barriers in order to continue cervical screening. Findings indicate that valuable insights have been gleaned from the women’s accounts surrounding practitioner’s method of service delivery. In addition, the aspects that these women put in place for themselves could also be considered by services and health providers.
Keywords: Interpretive Description; Disability; Women's health; Physical disability; Cervical screening; Disability health